2015
DOI: 10.5480/12-871.1
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Pediatric Camp Clinical for Pre-Licensure Education

Abstract: : This article describes the implementation and outcomes of a pediatric clinical education pilot project at a weekend overnight camp for children with special needs. Nine junior-level baccalaureate students participated in the immersion experience. The course skill inventory, an instructor-led postconference, a focus group session, and online forum entries were used to evaluate the experience. The evidence suggests that students gained a wide variety of psychomotor skills and patient-centered care attitudes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For example, some studies examined the impact of clerkship placements in specialized clinics for people with disabilities, 31 while others looked at nurses and occupational therapists' improvements after participating in a week-long summer camp for children with disabilities. 32 In the clinical setting, students found that they improved skills because they were able to engage with people with disabilities for extended periods, rather than a singular interaction. Furthermore, the out-of-clinic engagement, such as at camps, schools, or residential settings helped illustrate the non-medical and everyday lives of people with disabilities.…”
Section: Placements Experiential and Community-based Learningmentioning
confidence: 99%
“…For example, some studies examined the impact of clerkship placements in specialized clinics for people with disabilities, 31 while others looked at nurses and occupational therapists' improvements after participating in a week-long summer camp for children with disabilities. 32 In the clinical setting, students found that they improved skills because they were able to engage with people with disabilities for extended periods, rather than a singular interaction. Furthermore, the out-of-clinic engagement, such as at camps, schools, or residential settings helped illustrate the non-medical and everyday lives of people with disabilities.…”
Section: Placements Experiential and Community-based Learningmentioning
confidence: 99%
“…For example, some studies examined the impact of clerkship placements in specialized clinics for people with disabilities, 27 while others looked at nurses and occupational therapists' improvements after participating in a week-long summer camp for children with disabilities. 28 In the clinical setting, students found that they improved skills because they were able to engage with people with disabilities for extended periods, rather than a singular interaction. Furthermore, the out-of-clinic engagement, such as at camps, schools, or residential settings helped illustrate the non-medical and everyday lives of people with disabilities.…”
Section: Placements Experiential and Community-based Learningmentioning
confidence: 99%
“…Finding clinical placements for pediatric experiences can be challenging for nursing education programs located in rural settings (Hensel, Malinowski, & Watts, 2015). Rural hospitals typically do not have the numbers of pediatric patients necessary to provide individual pediatric experiences for an entire clinical group nor can rural community settings accommodate a full clinical group at one time.…”
Section: Pediatric Clinical For Nursing Students In Rural Areas: the Camp Nursing Experiencementioning
confidence: 99%
“…Online Journal of Rural Nursing and Health Care, 20(1) https://dx.doi.org/10.14574/ojrnhc.v20i1.603 147 supported and relaxed and 3) that scheduling was a barrier. Despite the scheduling issues, the authors indicated a desire to continue the camp experience for students as a pediatric clinical option (Hensel et al, 2015).…”
Section: Clinical Placement At Campmentioning
confidence: 99%